Mosaic variants in TNFRSF1A: an emerging cause of tumour necrosis factor receptor-associated periodic syndrome. (28th May 2022) - Assrawi, Eman; Louvrier, Camille; El Khouri, Elma; Delaleu, Jérémie; Copin, Bruno; Dastot-Le Moal, Florence; Piterboth, William; Legendre, Marie; Karabina, Sonia A; Grateau, Gilles; Amselem, Serge; Giurgea, Irina
Abstract: Objective: To identify the molecular basis of a systemic autoinflammatory disorder (SAID) evocative of TNF receptor-associated periodic syndrome (TRAPS). Methods: (i) Deep next generation sequencing (NGS) through a SAID gene panel; (ii) variant allele distribution in peripheral blood subpopulations; (iii) in silico analyses of mosaic variants using TNF receptor superfamily 1A (TNFRSF1A) crystal structure; (iv) review of the very rare TNFRSF1A mosaic variants reported previously. Results: In a 36-year-old man suffering from recurrent fever for 12 years, high-depth NGS revealed a TNFRSF1A mosaic variant, c.176G>A p.(Cys59Tyr), which Sanger sequencing failed to detect. This mosaic variant displayed a variant allele fraction of 14% in whole blood; it affects both myeloid and lymphoid lineages. p.(Cys59Tyr), a recurrent germline pathogenic variant, affects a crucial cysteine located in the first cysteine-rich domain (CRD1) and involved in a disulphide bridge. Introduction of a tyrosine at this position is expected to disrupt the CRD1 structure. Review of the three previously reported TNFRSF1A mosaic variants revealed that they are all located in a small region of CRD2 and that germinal cells can be affected. Conclusion: This study expands the localization of TNFRSF1A mosaic variants to the CRD1 domain. Noticeably, residues involved in germline TNFRSF1A mutational hot spots can also be involved in post-zygotic mutational events. Including our study, only four patients have been thus far reported with TNFRSF1A mosaicism, highlighting the need for a high-depth NGS-based approach to avoid the misdiagnosis of TRAPS. Genetic counselling has to consider the potential occurrence of TNFRSF1A mosaic variants in germinal cells.